The CHAIN WRITING METHOD IN LEARNING WRITING FOR INFORMATION TECHNOLOGY FACULTY STUDENTS: The Effectiveness - Yusniarsi Primasari; Hesty Puspita Sari; Nita Sutanti (JARES (Journal of Academic Research and Sciences), 2021)
This study purposes in determining the effectiveness of students writing ability on descriptive text being taught using the Chain Writing Method for the B class of Informatics Engineering Study Program Balitar Islamic University 2020/2021 academic year. This research is an experimental research, which uses the chain writing method to find out its effectiveness from student learning outcomes. The population of this study were first semester students of Informatics Engineering Study program which consisted of 21 students as a sample. The researchers applied one group pretest posttest. The sampling technique is random sampling. The method used is a quasi-experimental design. The pretest result done by Informatics Engineering students shown the average was 44.19%. The pre-test was conducted by researcher in March 2020. Then it can be concluded that their Writing Descriptive text ability are not good enough. The results of data analysis, known that the chain writing method is more effectively used in learning to write descriptive text for B class of Informatics Engineering students. It has significance difference in mean of determining by précising statistics of dependent T-test. From the calculating result of the t-test found that the t-value obtained was 5,959, while the required critical t-value at p> .05, the level of significance of the two tailed test is 2.086 (df = 20), p> .01 the two tailed significant level of test was 2.845 (df = 20). The data results of this research indicates that there is a significance difference in pretest and posttest score result. This proves that the chain writing method is effective method in learning the descriptive texts for the informatics engineering class in the 2020/2021 academic year.